Peningkatan Aktivitas Dan Kemampuan Mahasiswa Dalam Memecahkan Masalah Dengan Menggunakan Model Pembelajaran Group Investigation (GI) Pada Mata Kuliah Ekonomi Makro Semester Iv Di Universitas Hamzanwadi Tahun Ajaran 2019/2020 - Farhana Muhammad (Universitas Hamzanwadi, 2019)
This study aims to improve the activity and ability to solve problems in the material Characteristics of developing countries, economic problems and policies in developing countries and economic theories of development and the evolution and characteristics of the Pancasila economic system (SEP) in the fourth semester of the class B Faculty of Economics and Social Sciences, Hamzanwadi University. The form of research used is classroom action research (CAR). The subject of the research was the fourth semester students of Class B. The instrument used in this study was the observation sheet and the test results of students' ability to solve problems. The results showed (1) Group Investigation (GI) learning model can increase student activity in conducting discussions on Evolution material and the characteristics of the Pancasila economic system (SEP) with the percentage of students categorized as very active, active and quite active by 86.21% . (2) Group Investigation Learning Model (GI) can improve student outcomes in solving problems in the Indicators of successful learning outcomes that is equal to 75.86% of students who are capable.